Paradigm Shift in Digital Economic Law: Revitalizing Islamic Economic Law - Challenges and Opportunities - Nasri, Ulyan; Adiba, Elfira Maya (Et-Tijarie, 2023)
The development of digital technology has significantly transformed the global economic landscape. In this context, the paradigm of economic law has also undergone profound changes. This literature review investigates the paradigm shift in digital economic law, with a specific focus on revitalizing Islamic economic law in this era. The main objective of this research is to identify the challenges and opportunities presented by these changes and to explore how Islamic economic law can be applied in the increasingly complex digital economic context.The research methodology employed is a literature review using a descriptive-analytical approach. Data are obtained through the analysis of scholarly literature, journal articles, books, and other relevant sources discussing digital economic law and Islamic economic law. The data analysis involves a deep understanding of the paradigm shift in digital economic law and the challenges that arise, such as regulation, consumer protection, and transaction security. On the other hand, the research also explores the potential of Islamic economic law in providing a framework that aligns with the principles of Islamic economics within the digital economic ecosystem.The results of this research indicate that despite significant challenges in adapting Islamic economic law to the digital economy, there are substantial opportunities to promote ethical principles and economic justice. In this increasingly interconnected digital era, Islamic economic law can play a crucial role in shaping a more inclusive, sustainable economy aligned with ethical values. The implications of this research include the importance of developing regulatory frameworks that align with the digital economy while considering the values of Islamic economic law. It also underscores the need for greater awareness and understanding of the potential and contributions of Islamic economic law in the evolving digital economic context.